Alternative Advancements: Hyaluronic Acid Vs. Connective Tissue Graft In Black Triangle Management - Fathia Agzarine Deandra; Robert Lessang; Dimas Ilham Hutomo (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: The growing demand for aesthetic dentistry has increased the need to address the issue of the black triangle. This condition refers to the loss of the interproximal area leaving the gap in the gingival embrasure which eventually compromises the appearance of gingival harmony. Various treatment options have been explored to overcome the black triangle, from surgical to non-surgical approaches. Objective for this study is to compare the effectiveness between Connective Tissue Graft (CTG) and Hyaluronic Acid (HA) in black triangle management. Review: Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA)-adapted literature searches were conducted from four online databases (Pubmed, Google Scholar, Science Direct, and Embase) published in English from 2018 to 2023. A total of 1103 studies were retrieved, and following systematic review, 7 articles were selected as the inclusion criteria. Five studies employed HA as the therapeutic approach, while CTG was utilized in only two studies. Both treatments showed improvements in clinical parameters, such as increasing papila interdental height (PIH) and decreasing black triangle height (BTH). All the improvements are statistically significant. The recent trend in black triangle management suggests a shift towards the adoption of HA due to its minimally invasive procedures and high predictability results. Three out of five studies included stated that HA injection decreases BTH to 1mm at 6-month follow-up. Conclusion: HA presents itself as a promising alternative to the CTG for filling the papila deficiency, though it does not apply to all cases. Long-term studies are needed to observe the general use of HA for black triangle treatment.